Sahal Mahfudz's Sociological Approach to Islamic Legal Thought in Indonesia - Samad, Samad; Novita, Akne Nabila (Yayasan Insan Mulia Bima, 2025)
Scholarly disputes, which eventually gave birth to a methodology or ijtihad, are integral to the evolution of Islamic philosophy. The capacity to adjust to societal changes and needs is a key feature of this Islamic legal finding. Using a sociological lens, this study aims to delve more into KH Sahal Mahfudz's ideas. The literature review in this study is of a qualitative nature. Examining Islamic practices via a sociological lens is actually not a novel idea. It is widely acknowledged that this approach has deep roots in Islamic intellectual history, and this includes KH Sahal Mahfudz of Indonesia. In the realm of traditional pesantren, which has extensive experience with the study and development of fiqh, it would be greatly appreciated if ideas of social fiqh could be effectively articulated. A dynamic leap forward in fiqh theory can be achieved by expanding upon the concepts already present in social fiqh thought. As a first step, social fiqh aspires to integrate revelation's veracity with social reality. As part of the renewal movement of Islamic legal thinking in Indonesia, this alternative is vital in the quest to fit religious principles to social reality via the ever-changing cleansing.